Organizational-Based Self-Esteem and Organizational Identification as Predictors of Turnover Intention: Mediating Role of Organizational Trust - Oguegbe, Tochukwu Matthew; Edosomwan, Henry Samuel (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- This study aimed to examine the predictive role of organizational-based self-esteem and organizational identification on turnover intention while also studying the mediating effect of organizational trust among employees across five organizations. Design/Methodology- This study utilized the cross-sectional research design and quantitative approach for data collection. The study sample comprises 131 employees drawn from five organizations with a mean age of 33.15 years (SD, 7.97). Standardized instruments (questionnaires) were used for data collection. The IBM-SPSS Statistics and Hayes PROCESS macro (model 4) was used for testing the hypotheses and conducting the mediational analysis. Findings- The results of the study revealed a significant negative relationship between organizational-based self-esteem and turnover intention (β= -.33, p < .01), and also a significant negative relationship between organizational identification and turnover intention (β=-.29, p < .01). Organizational trust was also found to mediate both relationships. Practical Implications- The results of this study highlight the importance of organizational-based self-esteem, organizational identification and trust in reducing turnover intention. The study recommends that to keep employees in the organization, human resources management (HRM) needs to foster trust, build practice that will promote identification and attachment, and enhance the relationship between the organization and employees.